1992
DOI: 10.1007/bf00045554
|View full text |Cite
|
Sign up to set email alerts
|

Plant distribution in relation to the length of the growing season in a snow-bed in the Taisetsu Mountains, northern Japan

Abstract: The distribution pattern of plants was studied in an alpine snow-bed in six plots along a snow-melting gradient. Each plot consisted of two habitats with respect to the microtopography; the flat habitat and the mound habitat. The number of species per plot decreased with the shortened snow-free period. In the flat habitat, the dominant growth forms changed from the early exposed plots to the late exposed ones as follows; lichens ~ evergreen and deciduous shrubs ,---, forbs ~ graminoids ~ bryophytes. In the mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 22 publications
4
53
1
Order By: Relevance
“…The highest diversity appeared in the plots with intermediate depth of snow (class III and class IV). Kudo (1991Kudo ( 1992 and Kudo et al (1992) also found that plant species richness decreased in micro-sites where plants emerged very late from snow cover. This decline in the plots covered by deep snow might be due to the fact that only a subset of species could tolerate the conditions within a late snow bed.…”
Section: Discussionmentioning
confidence: 88%
“…The highest diversity appeared in the plots with intermediate depth of snow (class III and class IV). Kudo (1991Kudo ( 1992 and Kudo et al (1992) also found that plant species richness decreased in micro-sites where plants emerged very late from snow cover. This decline in the plots covered by deep snow might be due to the fact that only a subset of species could tolerate the conditions within a late snow bed.…”
Section: Discussionmentioning
confidence: 88%
“…A 1-month shift in phenology imposes a strong barrier to pollen flow between microhabitats, as S. herbacea flowers are only receptive to pollen for approximately 2 weeks (Beerling, 1998). Strong flowering time differentiation within short distances is not uncommon and has been reported in snowmelt gradients in Scandinavia for S. herbacea (Wijk, 1986b) and in other alpine species (Kudo, 1992;Kudo and Ito, 1992;Jones et al, 1997;Kudo et al, 1999;Shimono and Kudo, 2005;Hirao and Kudo, 2008;Shimono et al, 2009;Wipf et al, 2009;Elmendorf et al, 2012). Some of these exhibit genetically differentiated, phenologically isolated subpopulations Yamagishi et al, 2005;Hirao and Kudo, 2008;Shimono et al, 2009).…”
Section: Snowmelt Differences Results In Phenological Isolation But Nomentioning
confidence: 99%
“…All plots were located within 700 m distance. Snowbed vegetation composed of dwarf shrubs and forbs develops in these plots (see Kudo and Ito 1992 for species composition). We have monitored snowmelt pattern of these plots since 1988.…”
Section: Study Sitementioning
confidence: 99%
“…Such a heterogeneous snow distribution is a major factor creating diverse plant communities in alpine ecosystem (Billings and Bliss 1959;Kudo and Ito 1992). Although spatial pattern of snow dynamics is consistent among years, actual timing of snowmelt varies greatly from year to year reflecting inter-annual variation in climate conditions.…”
Section: Introductionmentioning
confidence: 99%